The Effect of Different Doses of Intravenous Dexmedetomidine on the Properties of Subarachnoid Blockade: A Systematic Review and Meta-Analysis - Mohammad K Al Nobani (16561248) (2020)
Background: Dexmedetomidine is a sedative and analgesic medication which has gained an increased usage as an adjuvant to both general and regional anaesthesia in recent years. In this systematic review and meta-analysis, we examined the changes to the characteristics of subarachnoid block when accompanied with intravenous dexmedetomidine. Our aim is to evaluate the effects of different doses of intravenous dexmedetomidine on the sensory and motor blockade duration of a single shot spinal anaesthetic and the incidence of any associated side effects. Methods: We searched published randomized clinical trials (RCTs) from January 1992 to April 2019 that investigated the use of IV dexmedetomidine with spinal anaesthesia. After considering our inclusion and exclusion criteria, we included 15 RCTs with 985 patients. We analyzed the duration of sensory and motor blockade and the related adverse effects in relation to different doses of IV dexmedetomidine. Results: Intravenous dexmedetomidine, with loading dose of 1 mcg/kg, prolonged the sensory blockade duration of spinal anaesthesia by a mean difference of 49.6 min, P<0.001, and motor blockade duration by a mean difference of 44.7 min, P<0.001, while a loading dose of 0.5 mcg/kg prolonged the sensory blockade by a mean difference of 43.06 min, P<0.001, and motor blockade duration by a mean difference of 29.09 min, P<0.001. Dexmedetomidine-related side effects were higher in patients receiving larger doses; the incidence of bradycardia was higher (OR=3.53, P<0.001) and incidence of hypotension showed a 1.29 fold increase when compared to the control group (P=0.065). Conclusion: The administration of intravenous dexmedetomidine in conjunction with spinal anaesthesia can significantly prolong the duration of both sensory and motor blockade. The use of larger loading doses of dexmedetomidine was associated with a larger side-effect profile with minimal beneficial changes when compared to lower loading doses. Other Information Published in: Local and Regional Anesthesia License: https://creativecommons.org/licenses/by/4.0/ See article on publisher's website: http://dx.doi.org/10.2147/lra.s288726